PENGARUH MODEL PROBLEM BASED LEARNING BERBANTU VIDEO ANIMASI STOP-MOTION TERHADAP LITERASI SAINS DAN SIKAP ILMIAH KELAS XI PADA MATA PELAJARAN BIOLOGI - Toni Efriyandika; Mujiati; Zulkefli Tambe; Rido Illah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research was motivated by the low Science literacy and scientific attitudes of students in the learning process. One of the learning and media models is the Problem Based Learning model and the Stop-Motion Animation video media. This study aims to determine the influence of the Problem Based Learning model assisted by Stop-Motion Animation videos on the Ability of Science Literacy and scientific attitudes of grade XI students in Biology subjects at SMA Negeri 16 Bandar Lampung. This research is a quantitative research with quasy experiment method. The study population was taken using 2 classes XI of science and the research sample consisted of XI IPA 8 as the experimental class and class XI IPA 9 as the control class. The total population consists of 50 learners with a control class of 25 learners and an experimental class of 25 learners.Based on the results of data analysis obtained from pretest and posttest data analyzed using the Independent Sample T-Test test to answer the hypothesis. The data obtained from the calculation of the hypothesis with an independent t-test sig value (2-tailed) which is 0.00 0.05 means that Ho is rejected Hi accepted So it can be concluded that the hypothesis in the study is accepted, meaning that there is an influence of the Problem Based Learning Model on Science Literacy and Scientific Attitudes of students. Keywords: Science Literacy; Problem Based Learning; Cell; Stop-Motion Animation video